Understanding the effect of moisture on the spreadability of inconel powders in powder bed fusion - Liao, Liyi (Nanyang Technological University, 2021)
This project intended to investigate the impact of moisture on the spreadability of Inconel powders (IN625R, IN718V, IN725R) in powder bed fusion by carrying out morphology and particle size distribution analysis via SEM, measuring moisture content with a moisture analyzer, and mapping the powder layer thickness via MATLAB. More satellites appeared on IN718V’s surface and the consecutive powder agglomeration, as well as IN725R’s narrow PSD, hinder the spreading of a uniform powder layer. In spite of the sphericity of IN625R powders, there was more moisture pick-up in dried status than in the as-received condition. Powder agglomeration in IN625R and IN725R powders also resulted in the reduction of layer thickness. Moderate recoater speed exhibited the best-balanced results of achieving desirable layer thickness with high layer uniformity. Other factors and additional moisture content measurement methods and their accuracies could be further explored to support this research.